2020
DOI: 10.3390/en13051228
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on Flow Resistance and Bubble Transport in a Helical Static Mixer

Abstract: Flow resistance and bubble transport in a helical static mixer were studied experimentally and numerically. The inline mixer increases the volume fraction of gas in liquids by breaking bubbles into smaller sizes with a micrometer size in the flow experiments. The gas–liquid flow was simulated by a combination of computational fluid dynamics and Taylor expansion methods of moments. The friction factor of the helical static mixer is much smaller than that of the Kenics static mixers. The pressure drop increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…A new correlation was proposed (Equation ()) with R 2 (coefficient of determination [COD]) = 0.95. DH=π0.25emD4wπ+22w/D0.0240.25emnormalm0.25em fmgoodbreak=2P0.25emDH0.25emε2ρ0.25emutrue¯2L0.25em fgoodbreak=1950.25emReL0.740.25em Equation () deviates by ±15% at most from the correlation proposed in Table 2 [ 37 ] and ±13% from the modified experimental friction factor (fm exp). [ 41,42 ] The difference between our experimental results and the correlations proposed by various authors was reduced after taking into account the influence of the geometric parameters of the KSM, such as porosity and hydraulic diameter. The remaining gap can be explained by the effect of the pipe diameter and the relative roughness.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…A new correlation was proposed (Equation ()) with R 2 (coefficient of determination [COD]) = 0.95. DH=π0.25emD4wπ+22w/D0.0240.25emnormalm0.25em fmgoodbreak=2P0.25emDH0.25emε2ρ0.25emutrue¯2L0.25em fgoodbreak=1950.25emReL0.740.25em Equation () deviates by ±15% at most from the correlation proposed in Table 2 [ 37 ] and ±13% from the modified experimental friction factor (fm exp). [ 41,42 ] The difference between our experimental results and the correlations proposed by various authors was reduced after taking into account the influence of the geometric parameters of the KSM, such as porosity and hydraulic diameter. The remaining gap can be explained by the effect of the pipe diameter and the relative roughness.…”
Section: Resultsmentioning
confidence: 76%
“…Single‐phase pressure drops with and without mixers, Kenics with six elements, were measured using a multi‐tube manometer. The comparative evolution (Figure 4) of the experimental data of this work using the Darcy friction factor (a method used for a modified KSM [ 40 ] ) with correlations established from friction factors determined pipe diameters of 12.7 mm, [ 35 ] 21 mm [ 36 ] as well as 30 mm, [ 36 ] and 20 mm [ 37 ] with aspect ratios of, respectively, 2.5, 2, and 1.5 showed that the modified pressure drop factor (Equation ()) [ 41,42 ] calculated using the experimental pressure drop values, the hydraulic diameter influenced by the presence of KSM (Equation ()), [ 37 ] and the porosity of KSM has the same shape as the Darcy coefficient reduced by a factor of 1.9 ()fm=f1.9. It was also noticed that the modified pressure drop factor was very close to the correlation mentioned in Table 2, [ 37 ] for 8110 < Re L < 18 940, which is equivalent to 4870 < Re h < 11 362.…”
Section: Resultsmentioning
confidence: 99%
“…Several advantages make them suitable to replace the classical equipment, among which are lower space requirements and energy demand thanks to the absence of moving parts. Further benefits include low operational costs, increased process safety, and better selectivity with respect to the reduction of byproducts reduction thanks to mixing intensification [43,45,46]. This has led to various applications in several fields, e.g., chemistry, pharmaceuticals, food, polymers, and water treatment.…”
Section: Integration Of Mixing Elements and Static Mixersmentioning
confidence: 99%
“…Nho et al [19] studied the total pressure losses of narrow channels with 11 different types of top structures incorporating ribs on the in-line turbine cascades, and found that the total pressure loss was smallest at the top of the double ribs and the slope groove on the pressure side. Fangyang Yuan [20] studied the flow resistance and bubble transport in a helical static mixer, and found that the pressure drop increases with the Reynolds number, and the increment is larger when the Reynolds number is higher. Ostanek and Thole [21] studied the loss in pressure drop along different forms of ribs, and identified a large loss of pressure of ribs with edges.…”
Section: Experimental Equipmentmentioning
confidence: 99%